296 Case Report: Pacemaker Lead-Induced Fibrosis Resulting in Right Atrial and Tricuspid Stenosis Managed with An Open Surgical Approach. (12th October 2021) - Russell, T; Lichtenstein, K; Bashir, J
Abstract: Pacemaker leads can result in localised inflammation and, over time, fibrosis. Rarely, this can significantly alter the anatomy of the heart and impair cardiac function. In this case, a fifty-year-old female had undergone pacemaker placement in her teens having experienced symptomatic bradycardia. Due to pacemaker pocket erosion, she had undergone a lead extraction where lead fragments had been left in-situ. Years after a new generator and leads were placed, she presented with symptoms of proximal venous congestion and superior vena cava (SVC) syndrome. A venogram demonstrated completely occluded brachiocephalic and innominate veins with significant adjacent venous collateralization. Computed tomography showed partial obstruction of the SVC and tricuspid stenosis. Initially, a decision was made not to intervene. After developing abdominal distension, she was diagnosed with hepatic congestion and cirrhosis secondary to elevated right sided pressures and right atrial congestion due to tricuspid stenosis. It was concluded that the patient's symptoms were the result of occluded proximal veins, SVC syndrome, and functional tricuspid stenosis, all of which were likely the result of fibrotic tissue secondary to pacemaker lead-induced inflammation. Due to the severity of her symptoms, the patient accepted the risks associated with surgical management. Intra-operatively, electrocautery was used to debride the fibrotic tissue inhibiting the leaflets of the tricuspid valve. This worked to great effect and additional valve repair/replacement was not necessary. Whilst the patient has been left with SVC syndrome, her tricuspid stenosis symptoms are greatly improved. To our knowledge, such a case has not been previously described.